Impact Des Eaux Usées Et Des Aménagements Urbains Sur La Répartition Des Espèces De Culicidae (Diptera Nematocera) Dans La Ville De Meknès (Maroc) - Nadia, Handaq; Abdelali, Blenzar (European Scientific Journal, ESJ, 2017)
In the Meknes region, urban and peri-urban green spaces are mainly irrigated by wastewater, whose flow has considerably increased in recent years due to the extent of urbanization. These agricultural areas along the three valleys of Bou Ishak, Boufekrane and Ouislane are an asset of the city of Meknes, but they are at the origin of the proliferation of culicidal species harmful to the urban population, especially during the summer season marked by the decrease in clear water from sources. The biotypological analysis of the breeding sites encountered in the studied perimeter, revealed the main elements that determine the distribution of culicidal species. This depends in large part on the situation of the deposits, either upstream of the discharges of the waste water or downstream of these discharges. Thus, deposits located in the southern suburbs of Meknes, upstream of domestic and industrial wastewater discharges, show an important specific richness with the presence of eleven species divided into four genera. On the other hand, in the lodgings located in the urban perimeter, characterized by polluted water, we noted the predominance of two species belonging to two genera Culex and Aedes. The reduction in the specific richness of these deposits is related to the degradation of water quality, mainly due to the discharge of domestic and industrial wastewater.